An investigation of the 85th percentile operating speed models on horizontal and vertical alignments for two-lane rural highways: A case study - Syed Khairi, Syed Abbas, Engr. (The Institution of Engineers, Malaysia (IEM), 2013)
Link to publisher's homepage at http://www.myiem.org.my/